Don't tell me how to die : a novel - Karp, Marshall (Blackstone Publishing, 2025)
I had it all: a fantastic husband, two great kids, an exciting career. Then at the age of forty-three, I found out I would be dead before my next birthday. I plan to spend every last waking minute searching for the perfect woman to take my place as Alex's wife.